Implementation of landscape design as elements in creating values for housing areas in Klang Valley, Malaysia - Mohd Shahli, FitryNadia; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zaidin, Nurbazliah (2014)
In Malaysia, the concern regarding the implementation of landscape design as one of the indicators for making a value to the house has never been more important. In terms of providing a significant value to the house is need to study. Subsequently, to enhance the quality of life and sustain a livable environment for future development seems crucial and related to the values of housing area. The impact on its values such as environmental value, social value and functional value toward a community becomes a priority. Therefore, this paper is aimed to identify the contribution of landscape design as an element in influencing the values of housing area in urban areas. The method specifically adopts triangulation methods of study consist of a collection of survey, interview and observation technique that conducted in selected housing area, in Klang Valley. The main findings show the involvement of landscape design in term of its planning, characteristic and elements can influence the value of house. It is hoped that this paper may provide significant information on the implication of landscape design towards influencing the values of the house and also attract prospect buyers in the future.